Nationalism, Authoritarianism, Fascism: Why in the Baltic States the Past Becomes the Future (Article Two) - N. M. Mezhevich (Управленческое консультирование, 2020)
The Great Patriotic War was not only the opposition of countries, but also the struggle of ideologies. Fascism was defeated, communist ideology and democratic practices won and began to compete among themselves. Mutual deterrence in post-war Europe contributed to fascism and neo-Nazism not becoming a threat to society.The weakening of external political governance and the collapse of the USSR led to a qualitative increase in nationalism in Eastern Europe. However, in the Baltic States, transformation of nationalism into authoritarianism, and authoritarianism into fascism, which took place in the 20th-40th years of the last century, is repeated again. Two articles are devoted to the specifics of this process. The first tells about the specifics of the political systems of the modern Baltics, the history of the Baltic countries and the genesis of fascist ideology in the Baltics. The second article is devoted to Baltic nationalism as a factor in the formation of authoritarian and fascist practices, the assessment of the prospects for the revival of fascism in the Baltics and the analysis of this danger for Russia. The anniversary of the Great Victory is not only an excuse for pride in the past, but also a good reason to find threats to the future.